Economics and crime: the cost of violence for the municipality of Governador Valadares, MG - Ribeiro, Hilton Manoel Dias (2021)
The municipality of Governador Valadares, MG, has approximately two hundred and eighty thousand inhabitants and remained in 5th place in the state ranking of violence in 2015. We measured, through the accountability methodology, public costs, private costs, and social losses resulting from violence. The results indicate that the aggregate value of these three cost categories, in the year 2015, reached approximately the equivalent of 5.8% of the municipal GDP.